Evidência de validade baseada na estrutura interna da versão em português brasileiro do Thyroidectomy-related Voice and Symptom Questionnaire (TVSQ) - Cândido, Ana Flávia de Sales (2021)
Thyroidectomy is a surgical procedure that can affect the functionality of the voice and swallowing, with a consequent impact on communication, food and quality of life. Early identification and monitoring of these conditions since the preoperative period is essential for decision making and the rehabilitation process. The Thyroidectomy Related Voice and Symptom Questionnaire (TVSQ) is a questionnaire for this purpose, already translated and adapted into Brazilian Portuguese, but with no evidence of validity based on the internal structure. The aim of this study is to develop evidence of validity based on the internal structure of the Brazilian Portuguese version of the Thyroidectomy-Related Voice and Symptom Questionnaire (TVSQ). This is an observational, cross-sectional and analytical validation study, with a quantitative approach. 395 responses to TVSQ were obtained, derived from three sources: face to-face interview, telephone contact and digital platform. The data were analyzed by means of factor analysis, seeking to reduce variables in factors by exploratory factor analysis and to confirm the structure proposed by confirmatory factor analysis. The exploratory factor analysis designated the retention of three factors composed of the 20 items of the TVSQ with a general Cronbach's alpha of 0.947, which implies a high internal consistency of the instrument. The confirmatory factor analysis through the adjustment indexes and the convergent and discriminant validities confirmed the structure of 3 factors organized in: Factor 1 called vocal symptoms; Factor 2 called oropharyngolaryngeal symptoms and Factor 3 called discomfort in swallowing, breathing and in the cervical-thoracic region. It is concluded that the application of structural equation modeling showed the validity based on the internal structure of the Brazilian Portuguese version of TVSQ, its structure being formed by three factors.